Implementation of Analytical Hierarchy Process (AHP) Method on Teacher Performance Appraisal Decision Support System - Erliyana Nurrahma; Berlilana, Berlilana (LPPM Universitas Potensi Utama, 2024)
Assessing the quality of education in a school often hinges on evaluating the performance of its teaching staff. Teachers play a pivotal role as professional educators shaping the learning experiences of students. Their performance evaluations not only serve as a benchmark for excellence but also as criteria for career advancements, such as promotions to higher positions or recommendations for teacher certification programs. To ensure these assessments are fair, consistent, and objective, it's crucial to employ a reliable evaluation method. The Analytical Hierarchy Process (AHP) emerges as a robust tool for this purpose. AHP offers a structured framework that facilitates comprehensive decision-making by allowing decision-makers to prioritize various criteria based on their relative importance. In the context of this study, data for the AHP analysis was gathered through questionnaires distributed to respondents. These questionnaires likely covered multiple aspects of teaching performance, such as instructional effectiveness, classroom management, and professional development. After collecting and analyzing the data using the AHP method, the results provided a weighted ranking of the teachers. According to the AHP analysis, Teacher C emerged as the top performer with a weight of 0.7604 or 76.04%. This indicates that Teacher C excelled in the evaluated criteria and demonstrated superior teaching skills. Following closely, Teacher B secured the second spot with a weight of 0.2079 or 20.79%. Lastly, Teacher A received the lowest priority with a weight of 0.0517 or 5.17%. These findings not only highlight the strengths and areas for improvement among the teachers but also offer valuable insights for school administrators to make informed decisions regarding promotions, certifications, and professional development opportunities.